Development and Comparison of Complementary Methods to Study Potential Skin and Inhalational Exposure to Pathogens During Personal Protective Equipment Doffing. (13th September 2019) - Therkorn, Jennifer; Drewry, David; Andonian, Jennifer; Benishek, Lauren; Billman, Carrie; Forsyth, Ellen R; Garibaldi, Brian T; Nowakowski, Elaine; Rainwater-Lovett, Kaitlin; Sauer, Lauren; Schiffhauer, Maggie; Maragakis, Lisa L
Abstract: Background: Fluorescent tracers are often used with ultraviolet lights to visibly identify healthcare worker self-contamination after doffing of personal protective equipment (PPE). This method has drawbacks, as it cannot detect pathogen-sized contaminants nor airborne contamination in subjects' breathing zones. Methods: A contamination detection/quantification method was developed using 2-µm polystyrene latex spheres (PSLs) to investigate skin contamination (via swabbing) and potential inhalational exposure (via breathing zone air sampler). Porcine skin coupons were used to estimate the PSL swabbing recovery efficiency and limit of detection (LOD). A pilot study with 5 participants compared skin contamination levels detected via the PSL vs fluorescent tracer methods, while the air sampler quantified potential inhalational exposure to PSLs during doffing. Results: Average PSL skin swab recovery efficiency was 40% ± 29% (LOD = 1 PSL/4 cm 2 of skin). In the pilot study, all subjects had PSL and fluorescent tracer skin contamination. Two subjects had simultaneously located contamination of both types on a wrist and hand. However, for all other subjects, the PSL method enabled detection of skin contamination that was not detectable by the fluorescent tracer method. Hands/wrists were more commonly contaminated than areas of the head/face (57% vs 23% of swabs with PSL detection, respectively). One subject had PSLs detected by the breathing zone air sampler. Conclusions: This study provides a well-characterized method that can be used to quantitate levels of skin and inhalational contact with simulant pathogen particles. The PSL method serves as a complement to the fluorescent tracer method to study PPE doffing self-contamination. Abstract : A new method is pilot tested against the fluorescent liquid tracer method for quantifying skin and inhalational exposure to pathogens during personal protective equipment doffing. The new method uses fluorescent polystyrene latex spheres to simulate pathogen particles.